Theoretical foundations of calculation cylindrical parts tank car boilers using the MathCAD environment (Transport systems and technologies, 2024)
The article is devoted to the numerical calculation of the cylindrical part a tank car boiler, which is represented as a single-layer shell, and the study of its stress-strain state using the provisions of the semi-momentum theory shells. In some cases, under actual operating conditions of a tank car boiler, when the base metal wears out under the influence of corrosive phenomena arising from the interaction an aggressive environment and a storage and transportation tank, it becomes necessary to assess the stress-strain state and search for the most dangerous areas. The authors of this article propose a calculation algorithm that allows determining the stress state cylindrical shell of a structure, taking into account the decrease in metal thickness when corrosion occurs, using the method of calculated sections in the MathCAD software environment. The constructed mathematical model makes it possible to determine: the values of longitudinal and transverse displacements a flexible homogeneous shell of constant stiffness under the acting combined load; the values of normal forces, bending moments, and equivalent stresses in accordance with the adopted design scheme of the cylindrical part the boiler. The simplicity of implementing the proposed numerical algorithm makes it possible to use it in engineering practice, for example, during technical inspections and making decisions on the further safe operation tank car boilers according to the adjusted methodology at the early stages of research
Keywords: boiler; cylindrical part; shell; method of design sections; equivalent stresses; algorithm